Cyanide-free separation of high pyrrhotite Zn-S bulk concentrate. (15th August 2021) - Weiyong, Cui; Yingchao, Liu; Lixiao, Liang; Jianhua, Chen
Highlights: NOD shows powerful depression on pyrite and pyrrhotite. NOD has little effect on the flotation of marmatite. NOD can replace NaCN in zinc-sulfur bulk concentrate flotation. Abstract: A mixture of green organic compounds (MOC) with powerful depression to both pyrite and pyrrhotite was introduced to replace NaCN in the separation of highly complicated Zn-S bulk concentrate. The results of single, batch as well as pilot flotation tests indicated its excellent selective depression in the Zn-S bulk concentrate flotation. Especially, the comparison of the pilot tests showed an evident improvement in overall concentrate grade as well as Zn recovery with the mixed depressant MOC replacing NaCN, and the corresponding values were 3.03% and 5.01%, respectively.